PENGETAHUAN PEMANDU WISATA TENTANG PERTOLONGAN PERTAMA PADA KECELAKAAN WISATA AIR DI WILAYAH TANJUNG BENOA - Sriwandayani, Ni Luh Ari; Yanti, Ni Luh Putu Eva; Sanjiwani, Ida Arimurti (Coping: Community of Publishing in Nursing; Vol 9 No 6 (2021): Desember 2021DO - 10.24843/coping.2021.v09.i06.p14, 2021)
Watersport tourism is a tourist activity underwater using tourist facilities and infrastructure. Watersport tourism is tours that are extreme and dangerous because it can cause harm (physical hazard). Appropriate first aid knowledge is needed by watersport tour guides to reduce the mortality and morbidity of victims because the level of knowledge will affect the techniques of handling accident victims before being taken to the hospital. This study aimed to determine factors related to the knowledge level of tour guides about first aid in water tourism accidents at watersport Tanjung Benoa. This research was a descriptive correlational with a cross-sectional design. The stratified random sampling technique was used to determine 127 respondents. Data were analyzed using the Gamma test. The results of this study showed that the length of work (p = 0,000, r = 0.51) and training experience (p = 0.006. R = 0.42) have a significant relationship with first aid knowledge. On the other hand age, level of education, and sources of information were not related significantly to first aid knowledge (p> 0.05). It’s recommended that the company of watersport conduct training on first aid techniques regularly for water tour guides.